2014
DOI: 10.1118/1.4865811
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study demonstrating potential association between breast cancer image‐based risk phenotypes and genomic biomarkers

Abstract: Purpose: In this pilot study, the authors examined associations between image-based phenotypes and genomic biomarkers. The potential genetic contribution of UGT2B genes to interindividual variation in breast density and mammographic parenchymal patterns is demonstrated by performing an association study between image-based phenotypes and genomic biomarkers [single-nucleotide polymorphism (SNP) genotypes]. Methods: This candidate-gene approach study included 179 subjects for whom both mammograms and blood DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…After adjustment for planar mammographic percent density (PD), each feature attenuated only slightly and retained statistical significance; however, simultaneous inclusion of these features in a model with PD did not significantly improve the ability to predict breast cancer [8]. Other studies have shown that differences in texture and density features are related to predisposing mutations and tumor type including BRCA1/BRCA2 mutation carriers [1214] and estrogen receptor (ER) status [15–17]. Thus, the density patterns of the parenchymal tissue have attracted clinical attention because of their potential to offer additional information about subtype and cancer biology.…”
Section: Introductionmentioning
confidence: 99%
“…After adjustment for planar mammographic percent density (PD), each feature attenuated only slightly and retained statistical significance; however, simultaneous inclusion of these features in a model with PD did not significantly improve the ability to predict breast cancer [8]. Other studies have shown that differences in texture and density features are related to predisposing mutations and tumor type including BRCA1/BRCA2 mutation carriers [1214] and estrogen receptor (ER) status [15–17]. Thus, the density patterns of the parenchymal tissue have attracted clinical attention because of their potential to offer additional information about subtype and cancer biology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a Bayesian Artificial Neural Network algorithm, can distinguish the appearance of the parenchyma in patients with or without BRCA1/2-related breast cancer. 35,36 Potentially, the gist signal that humans detect could be a marker for one or more genetic subtypes. This is a question that our current data cannot address but would be worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the literature lacks large-scale longitudinal studies monitoring longitudinal changes in automated parenchymal texture descriptors over successive mammograms, which could elucidate the mechanisms of breast cancer development [ 11 ] and the causal relations between the texture risk scoring and breast cancer [ 102 , 103 ]. Finally, crucial questions to be addressed in such rich datasets are the causes of inter-woman variation in mammographic parenchymal patterns [ 104 , 105 ] and in the relation of texture risk markers to the subsequent location and grading of tumors, disease mortality, and treatment effects [ 20 , 21 ].…”
Section: Future Directionsmentioning
confidence: 99%